A ideia de crise de representatividade e a democracia participativa como estrutura de (re)legitimação do exercício do poder político - Teixeira, Igor Moura Rodrigues (2016)
We can no more make sense of what we mean by participatory democracy without reference to the eminent capitalist(-liberal) one. At the same time, the force of that duality is propelled by the great crisis of contemporary institutions and practices that stand in relation to the issue of representativeness in the light of modernity. The kind of liberal democracy we get in mind is, in a broad sense, the one emerged in parallel with the new capitalist economic order, intensified during the eighteenth century, and culminated in the nineteenth century. In a nutshell, it does mean that one has a legal system in order to safeguard the interests of private capital and individuals, supported essentially by a non-working-class government. Regarding this scheme which is not a done deal, it´s important to better understand the critique addressed to liberal democracy by means of political empowerment as well as the foundations of the state. By the way, one must figure out that the participatory democracy will really take place when overcoming the liberal one only following these steps: an increase of the consciousness about the political education behind the capitalism-liberalism orthodoxy, as consequence we can think of (or be open to) new alternatives which could be more sensible and democratically legitimate.